Corrosion Inhibition of Mild Steel in Sodium Chloride Solution by Nickel Complex of 1-(8-hydroxy quinolin-2yl-methyl) Thiourea - Abuthahir, S. S. Syed; Vijaya, K.; Abdul Nasser, A. Jamal; Karthikeyan, C. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
The Corrosion inhibition efficiency of an inhibitor namely Nickel complex of 1-(8-hydroxy quinolin-2yl methyl) thiourea (Ni-HTF) in controlling corrosion of mild steel immersed in aqueous solution containing 60 ppm Cl- has been investigated by polarization method. The formulation consisting of 60 ppm of Cl- and 50 ppm of Ni-HTF offers good inhibition efficiency of 80 %. Polarization study reveals that this formulation functions as a cathodic inhibitor. UV-Visible spectral analysis was used to detect the presence of iron-inhibitor complex. The surface morphology has been analyzed by SEM and EDAX.